Study on Liquid Metal Embrittlement Susceptibility of T91 Exposed to Liquid Lead-Bismuth Eutectic - Jie Zhang; Bo Qin; Bin Long (Metals)
In this study, slow strain rate tensile tests (SSRT) were performed on T91 in lead-bismuth eutectic (LBE) with saturated oxygen to investigate the effects of temperature (350 °C, 450 °C, and 550 °C), strain rate (1 × 10−5/s and 2 × 10−6/s) and pre-exposure conditions (time, oxygen concentration) on the sensitivity to liquid metal embrittlement (LME). The results revealed that the embrittlement sensitivity of T91 in LBE is significantly influenced by temperature. LME was observed in T91 at 350 °C and disappeared when the temperature increased to 550 °C. Additionally, T91 exhibited increased sensitivity to LME at low strain rates, indicating that low strain rates promoted the occurrence of LME. Finally, through different pre-exposure conditions, it was found that the obvious LME phenomenon would only occur when the oxygen concentration was poor and the pre-exposure time was long (48 h), indicating that pre-exposure conditions have a crucial impact on the occurrence of LME.